AB0650 PERSPECTIVES AND UNMET NEEDS OF PATIENTS WITH POOR PROGNOSIS SYSTEMIC SCLEROSIS ON AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANTATION CARE: A QUALITATIVE STUDY. (June 2019) - Bresser, Carolijn de; Spierings, Julia; Rhijn-Brouwer, Femke van; Pieterse, Arwen; Vonk, Madelon; Voskuyl, Alexandre; Vries-Bouwstra, Jeska de; Kars, Marijke; van Laar, Jacob M.
Abstract : Background: Autologous hematopoietic stem cell transplantation (HSCT) can induce long-term remission in patients with diffuse cutaneous systemic sclerosis (dcSSc). Nevertheless, it is an intensive treatment with risk of treatment-related mortality and associated adverse events requiring long-term hospital admission. Little is known about the psychosocial impact of HSCT on patients with dcSSc. Additionally, post-discharge care is currently not standardized. Objectives: To gain more insight in the experiences of patients during and after HSCT and to identify unmet needs in current care. Methods: Semi-structured interviews were conducted with dcSSc patients that underwent HSCT in four academic hospitals in the Netherlands. Interviews were transcribed verbatim and analyzed with NVIVO12. Results: Eight patients were interviewed (5 males and 3 females, mean age 48 years (SD 10), mean disease duration 4.6 years (SD 1.9), mean time since HSCT 3.2 years (SD 2.4). At inclusion mean SHAQ was 1.3 (SD 1.1) and mean EQ5D-5L 0.86 (SD 0.21). While patients were satisfied with the frequent, low-threshold contacts with physicians and nurses, the decision-making process followed by HSCT and recovery was mentally taxing. Although patient education was experienced as extensive pre-treatment, participants reported they only felt the real impact of it during therapy. Patients felt anxious throughout the hospital stay and they could not recall most events from that period. Feelings of losing control over health and over time were frequently described. Support of family and friends was important during treatment. Apart from the practical aid, they provided emotional support, helping to cope with emotions and to find purpose. Furthermore, a specialized nurse involved in psychosocial support and care management was highly valued. Still, participants felt lonely and misunderstood due to invisible disabilities, such as fatigue and pain. After HSCT, patients experienced more physical limitations than they expected, i.e. low energy levels and limited hand function. They worried about contracting infections and relapse risk. Professional rehabilitation was often hindered. There were unmet needs. Patients preferred to be better informed about what to expect after admission. Structured and written instructions should include themes such as self-management, practical tips and prognosis of recovery. Participants would advise peers to keep a diary and even take photos during HSCT and hospital stay, in order to help recollect and assimilate past events. Peer-support was recommended by most patients. Conclusion: HSCT had a large impact, both physical and emotional. We identified unmet needs regarding patient education on rehabilitation and psychosocial support in the period following HSCT. Disclosure of interests: Carolijn de Bresser: None declared, Julia Spierings Grant/research support from: Boehringer ingelheim, Femke van Rhijn-Brouwer: None declared, arwen Pieterse: None declared, Madelon Vonk Grant/research support from: Madelon Vonk has received unrestricted research funds from actelion and therabel, Consultant for: Madelon Vonk was a consultant for actelion, Boehringer-Ingelheim, Speakers bureau: actelion, Boehringer-Ingelheim, Roche, alexandre Voskuyl: None declared, Jeska de Vries-Bouwstra: None declared, Marijke Kars: None declared, Jacob M. van Laar Grant/research support from: Genentech, Consultant for: F. Hoffmann-La Roche